2019
DOI: 10.3390/healthcare7030093
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Sleep Endoscopy: Technique, Indications, Tips and Pitfalls

Abstract: Drug-induced sleep endoscopy (DISE) is a diagnostic tool to assess the upper airway of snorers and obstructive sleep apnea patients in conditions that mimic natural sleep. Although DISE appears simple and similar to awake endoscopy, there are many aspects that need to be standardized in order to obtain reliable and reproducible information. In this article, we will recommend how to reliably perform DISE, its indications, and how to obtain and interpret the information of the upper airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Propofol has consistently established itself as the gold standard for sedation in this setting as it combines overall safety and time effectiveness. Moreover, several studies have shown that findings in DISE tests conducted under propofol sedation led to appropriate surgical outcomes [11,12] . Propofol can be administered in boluses or as an infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has consistently established itself as the gold standard for sedation in this setting as it combines overall safety and time effectiveness. Moreover, several studies have shown that findings in DISE tests conducted under propofol sedation led to appropriate surgical outcomes [11,12] . Propofol can be administered in boluses or as an infusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the patient does not tolerate CPAP, DISE can be utilized to determine the possible effectiveness of alternative treatments including upper airway surgery and oral devices. DISE cannot be safely performed in patients with American Society of Anesthesiologists class 4, pregnancy, or allergies to sedative agents [17]. A high apnea-hypopnea index (AHI) score is not considered as a contraindication for DISE [17].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…DISE cannot be safely performed in patients with American Society of Anesthesiologists class 4, pregnancy, or allergies to sedative agents [17]. A high apnea-hypopnea index (AHI) score is not considered as a contraindication for DISE [17].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…This test may allow treatment customizing based on the respective obstruction site and pattern, positively impacting the outcome 14 , 15 . However, DISE requires standardization to obtain reliable information, which depends on the used sedation protocol 16 , encouraging the search for easier methods to predict the site and type of UA collapse.…”
Section: Introductionmentioning
confidence: 99%